Product Responsibility and Licensing of Skincare Product Labels in The Perspective of Justice - Zhou, Valerie; Pakpahan, Kartina; Pakpahan, Elvira Fitriyani (JURNAL MERCATORIA, 2025)
This article aims to analyze skincare product label licensing regulations in Indonesia, examine product liability and label licensing for skincare products from the perspective of justice, and explore efforts to combat criminal acts involving the distribution of skincare products that is failed to meet the quality also the safety standards. The problem is focused on the discovery—at the beginning of 2025—of 16 cosmetic items containing harmful and/or prohibited substances, including 10 contract-manufactured products and 6 imported products, and the necessity to ensure that all skincare products on the market comply with established quality and safety standards. In order to address this problem, the theoretical frameworks of product liability theory, justice theory, and crime prevention theory are used. The data is gathered through a review of literature and sujected to qualitative analysis. This study ultimately finds that that improved dissemination of regulatory information, stricter enforcement by BPOM, and awareness among all relevant parties are required to ensure consumer protection and the integrity of skincare product labeling.